1995
DOI: 10.1159/000244157
|View full text |Cite
|
Sign up to set email alerts
|

Maternal-Fetal Folate Status and Neural Tube Defects: A Case Control Study

Abstract: The object of this study was to explore the role of folate in the pathophysiology of neural tube defects (NTD). Maternal and fetal serum and red blood cell folate were assayed in 14 cases of NTDs and compared with 14 controls with other malformations and matched for gestational age (range 18–36 weeks). In mothers of NTD fetuses, serum folate (5.2 ng/ml), red blood cell folate (294 ng/ml) and the folate methylation rate (65%) were significantly lower than in controls (6.6 and 399 ng/ml, respectively, and 77%). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
5

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 18 publications
1
10
0
5
Order By: Relevance
“…RBC folate concentrations varied widely between subjects, especially in the high folate group. This suggests that RBC folate may be preferable to serum or plasma folate for the prediction of NTD risk (Bunduki et al, 1995;Daly et al, 1995). Brown et al showed that a folate concentration of X400 ng/ml in early pregnancy decreased the risk of NTD (Brown et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…RBC folate concentrations varied widely between subjects, especially in the high folate group. This suggests that RBC folate may be preferable to serum or plasma folate for the prediction of NTD risk (Bunduki et al, 1995;Daly et al, 1995). Brown et al showed that a folate concentration of X400 ng/ml in early pregnancy decreased the risk of NTD (Brown et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The precise impact of folate marginal folate deficiency remains unkown. However, the evidence is now reasonably strong that women of childbearing age with low folate sta tus are at higher risk of having a pregnancy affected with spina bifida or other neural tube defects [58]. Furthermore, compromised fo late status is believed to be associated with a rise in serum homocysteine, particularly among those who are heterozygous for the gene homocystinuria.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 One study observed a significant difference in erythrocyte folate quantification between case and control mothers, which was not observed when quantifying serum folate. 31 However, quantification of erythrocyte folate is more complex to perform 29.30 and, for this reason, many studies have measured serum folate. 5,[32][33][34] In addition, a recent study has indicated that serum folate assays provide information that is equivalent to erythrocyte folate measurements for attempting to determine folate deficiency.…”
Section: Resultsmentioning
confidence: 99%